1983
DOI: 10.1128/iai.42.3.863-868.1983
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies against Neisseria meningitidis lipopolysaccharide

Abstract: A cell line producing monoclonal antibodies directed against a lipopolysaccharide component of Neisseria meningitidis group A has been established. These antibodies reacted with only one of three lipopolysaccharide serotyping strains of group A meningococci by coagglutination, enzyme-linked immunosorbent assay, and Western blotting techniques. A Western blot analysis showed that a NaOH digest of lipopolysaccharide was detectable by the serotype-specific antibody. The monoclonal antibodies cross-reacted with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Schneider et al showed that a MAb raised against an L8 meningococcal LOS bound a 3.6-kilodalton (kDa) component (22). Similarly, Sugasawara identified a MAb (MCA14.2) which bound a LOS component of the same Mr made by two different L10 strains (24). In this study, we sought to identify serotype-specific LOS of group A meningococci by SDS-PAGE and by their binding of MAbs.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Schneider et al showed that a MAb raised against an L8 meningococcal LOS bound a 3.6-kilodalton (kDa) component (22). Similarly, Sugasawara identified a MAb (MCA14.2) which bound a LOS component of the same Mr made by two different L10 strains (24). In this study, we sought to identify serotype-specific LOS of group A meningococci by SDS-PAGE and by their binding of MAbs.…”
mentioning
confidence: 94%
“…This has improved the definition of these systems over that provided by polyclonal serum and made them efficient and available for field epidemiologic studies (19). Improved electrophoretic separation of LOS (21) and the availability of MAbs (24) have provided tools with which to study the molecular basis of LOS serotypes and to develop a more complete, rational, and efficient system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The LPS preparations were further characterized by the immunoblot technique to evaluate the antigenic relationship among the multiple bands seen on silver-stained gels. To our knowledge, this is the first report in which this technique has been used to examine heterogeneous LPS from Enterobacteriaceae, although Sugasawara et al [17] recently reported on the use of a monoclonal antibody to detect Neisseria rneningitidis LPS b2 4). Blots were developed with anti-O6 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Purified antigens have been used for the immunization in the majority of studies (Galloway et al 1984;Durham et al 1988;Yamaguchi et al 1989;Kabir 1991;Choi et al 1992;Daya-Mishne and Shabtai 1992). Antibodies against whole cells have been produced successfully (Sugasawara et al 1983;Bogard et al 1987;Applemelk et al 1988;Vernon-Shirley and Burns 1992). No reports exist, to our knowledge, on antibodies raised against S. putrefaciens.…”
Section: Discussionmentioning
confidence: 99%